1993
DOI: 10.1016/0378-1097(93)90220-v
|View full text |Cite
|
Sign up to set email alerts
|

Xylose and arabinose utilization by the rumen bacterium Butyrivibrio fibrisolvens

Abstract: The rumen bacterium Butyrivibrio fibrisolvens strain D1 co-utilized xylose and glucose in batch culture, but there was a marked preference for glucose over arabinose. When both pentoses were provided, xylose was preferred over arabinose. Strain D1 co-utilized a combination of either pentose and cellobiose, but preferred over maltose. Pentose sugars were depleted less rapidly in the presence of sucrose than controls containing only pentose. In contrast, B. fibrisolvens strain A38 exhibited a strong preference f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

1994
1994
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 7 publications
1
11
1
Order By: Relevance
“…Previous work with B. fibrisoluens indicated that glucose and xylose were co-utilized but utilization rates of each sugar in dual substrate incubations were slower than rates in cultures provided with only a single carbohydrate [4]; this result suggested that the presence of glucose influenced xylose utilization. An interaction between xylose and glucose utilization was also evidenced by the fact that pulses of each sugar significantly decreased the utilization of the other sugar; a mutual non-competitive inhibition of transport was apparently responsible for these observations.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…Previous work with B. fibrisoluens indicated that glucose and xylose were co-utilized but utilization rates of each sugar in dual substrate incubations were slower than rates in cultures provided with only a single carbohydrate [4]; this result suggested that the presence of glucose influenced xylose utilization. An interaction between xylose and glucose utilization was also evidenced by the fact that pulses of each sugar significantly decreased the utilization of the other sugar; a mutual non-competitive inhibition of transport was apparently responsible for these observations.…”
Section: Discussionmentioning
confidence: 87%
“…Transport activity of cells grown on different substrates suggested that xylose uptake was inducible, but the exact regulatory mechanisms controlling the expression of pentose permeases requires further study. Even though sucrose and cellobiose cultures had very low transport activity, cultures provided with either disaccharide and xylose showed at least some co-utilization of both sugars [4]; this result further implied that inductive control regulated xylose permease expression. In contrast, the strong preference for glucose over arabinose noted in the present as well as previous work [4] suggests that, in addition to induction, a level of repressive control exists in the case of arabinose transport.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Fibrolytic ruminal bacteria are able to degrade the hemicellulose of plant materials and utilize pentose sugars with glucose. Butyrivibrio fibrisolvens was reported to simultaneously consume glucose and xylose, although this effect was strain specific (Marounek & Kopecny, 1994;Strobel & Dawson, 1993). Ruminococcus albus consumed xylose and glucose simultaneously but the dominant repressor was cellobiose (Thurston et al, 1994).…”
Section: Discussionmentioning
confidence: 99%